Nurturing critical thought in children by reframing teachers’ approaches - a Portuguese case-study - Ramos, M. (4th International Conference on Psychology and Allied Sciences - Positive Schooling: A Heaven for Holistic Development - Margao 16-18 January 2016, 2016)
Progressive motorization as a key component of urbanization processes has induced in most regions of the world an alarming rate of sedentarism that has led to unprecedented calls from the global public health sector to tackle child obesity. The European Union has recently set specific goals to break the generalized use of private motorized vehicles in urban centres, with a triple objective: - reduce aerial pollution - minimize congestion - foment active mobility A growing effort has been evident in tackling the problem through education, a various programmes have been set in motion to introduce these issues in schools' curricula and their social integration practices. This means that European schools have been affected with direct responsibility in conveying these messages to students and their families, and thus produce comprehensive changes of behaviour. This means that teacher training is a key factor in the effective educative process in this area I intend to present a case-study where teachers training courses, coupled with projects directed at children, have been the base for this new education responsibility, in Portugal.